Model Peningkatan Pemahaman Literasi Media Sosial di Kabupaten Sleman - Popi Andiyansari (Jurnal Ilmiah Komunikasi Makna, 2019)
Social media is currenly one of the most used communication media by the community. The number of users of social media is not balanced with an understanding of ethics, danger, and how to counter information wisey. The ITE Law has been implemented since 2012 but does not increase the understanding and limits of users in social media. This study aims to improve public understanding of social media literacy and be able to control potentially unlawful interactions. The research method uses a quantitative approach by measuring the level of understanding of media literacy done twice, namely at the beginning of the study and the end of the study. This research is combine with treatment in the form of : socialization an practical guidance on ethics on social media. The result of this study are in the form of signifivantly increasing understanding of media literacy. The result were also obtained, the respondents did not understand the ethics and laws governing the use of social media.